DYNAMIC OF SEA LEVEL ANOMALY OF INDONESIAN WATERS - Bisman Nababan; Sri Hadianti; Nyoman M.N. Natih (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
A trend in sea level rise as a result of global warming could be a threat to small islands and coastal areas in Indonesia. The objective of this study was to determine the trend and variability of mean sea level anomaly (MSLA) in Indonesian waters during the 20 years of observation. The data used in this study were monthly MSLA data obtained from the AVISO website (ftp://ftp.aviso.oceanobs.com). Supporting data were the Southern Oscillation Index (SOI) (http://www.gom.gov.au/climate/enso), Dipole Indian Mode (DIM) index (http://gcmd.nasa.gov/records/GCMD_Indian_Ocean_Dipole.html), and the Pacific Decadal Oscillation (PDO) index (http://research.jisao.washington.edu/pdo/). Eigth stations of Indonesian waters were selected to study the variability of MSLA. In general, MSLA variabilities of Indonesian waters had a seasonal pattern, positively correlated with the SOI index, and negatively correlated with DIM and PDO indexes. The partial correlation of DIM was more dominant in west of Sumatra (r=-0.52) and south of Java (r=-0.44), PDO was more dominant in the northern waters of Papua (r=-0.37) and Makassar Strait (r=-0.33), and SOI was more dominant in northern Papua (r=0.52) and less toward the west of Indonesian waters. Overall, the MSLA variability of Indonesian waters can be explained by the variabilities of SOI, DIM, and PDO indexes with the lowest value in Natuna waters by 12% (R2=0.12) and the highest value in the northern waters of Papua by 54% (R2=0.54). Interannual variabilities were observed during ENSO events (SOI<-10) along with the maximum value of DIM index resulted in the lowest value of MSLA. Meanwhile, the highest value of MSLA was found during La Nina events (SOI>10) in conjunction with a minimum value of DIM and PDO indexes. The average rate of sea level rise in Indonesian waters was 5.84 mm/yr, almost two times higher than the average rate of global sea level rise (3.2 mm/yr). Keywords: mean sea level, anomaly, SOI, DIM, PDO, interannual, ENSO